Western Riding - Hughes, Mary (Philadelphia : Chelsea House Publishers, 2002)
Presents the history of western riding, including the Pony Express, rodeo, reining competition, quarter horse racing, and more.
Includes bibliographical references (p. 62).
Keywords: Western riding -- Juvenile literature; Horsemanship -- Juvenile literature; Western riding; Horsemanship